Biofabrication : micro- and nano-fabrication, printing, patterning and assemblies - Forgacs, Gabor; Sun, Wei (Amsterdam : Elsevier Science, 2013)
Biofabrication is a novel, inherently cross-disciplinary scientific field that focuses on biomanufacturing processes (technologies, materials, devices, models). This is the first book that presents the range of biofabrication technologies (cell printing, patterning, assembling, 3D scaffold fabrication, cell/tissue-on-chips) as a coherent micro-/nano-fabrication toolkit. The book is designed as a practical guide to these key emerging technologies, with real-world examples to help readers gain a working knowledge of how to apply biofbrication techniques.
Includes bibliographical references and index.
Keywords: Bioengineering; Microfabrication